STUDY ON THE INFLUENCE OF THE THREE-DIMENSIONAL MORPHOLOGY OF THE GEAR PITTING PITS ON STRESS CONCENTRATION OF TOOTH SURFACE - LI YouHua; CHEN Chao; YANG ShiHao; ZHANG ZhiHong; WANG Jun; LIU ZhongMing (Jixie qiangdu)
In order to study the influence of the three-dimensional appearance of the gear pitting pits on the stress concentration of the tooth surface, the effect of pitting pits with different shapes on stress concentration factor of gear was analyzed by finite element method. By changing the length, width and depth of ellipsoid pitting pits, the influence of different length-width ratio and depth-width ratio on stress concentration factor was analyzed, and the approximate calculation model of stress concentration factor of ellipsoid pitting pits was established. According to the contact fatigue test data of a gear, the calculation model established by this method was analyzed and verified, and the influence of the change of pitting pit size on the stress concentration factor of the gear was further analyzed and discussed. The results show that: the stress concentration of ellipsoid pits on the tooth surface was the most obvious, followed by conical pits, pentagonal pits and triangular pits when the basic size of pitting pits was the same. The stress concentration factor increases with the increase of depth-width ratio and length-width ratio of ellipsoidal pit.